If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 1 = x + -8 Reorder the terms: 1 + 6x = x + -8 Reorder the terms: 1 + 6x = -8 + x Solving 1 + 6x = -8 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 1 + 6x + -1x = -8 + x + -1x Combine like terms: 6x + -1x = 5x 1 + 5x = -8 + x + -1x Combine like terms: x + -1x = 0 1 + 5x = -8 + 0 1 + 5x = -8 Add '-1' to each side of the equation. 1 + -1 + 5x = -8 + -1 Combine like terms: 1 + -1 = 0 0 + 5x = -8 + -1 5x = -8 + -1 Combine like terms: -8 + -1 = -9 5x = -9 Divide each side by '5'. x = -1.8 Simplifying x = -1.8
| 4x+7y+2x+4y=180 | | 0.36p+0.26=386 | | -2t+22=10 | | -2+4w=14 | | 14(9-7)+x=30 | | 4g+8=2g+14 | | 5(1+4b)-3=-118 | | .25(4r-8)=r-2 | | 3z=12-33 | | 24=5y+3.89 | | -32=-7-12+3n | | 5x-7=.66 | | 8y+2=165.8 | | 3x+1-2x+2-4=-3-6x | | 4x^2+9x+5= | | a^3+a^2-4a-4= | | 5x-7=.666666666667 | | g-h=5g | | 5x^2-6x-4=0 | | 3x-4-2x=2x-20-2x | | 3m+12=7m | | 2d+.10=.60 | | -16.2+-18.5= | | 8m-8=m+7m | | 5(y)-3=19 | | -9.1+5.6= | | 3(6)-3(6)+1(2)=0 | | 5x-5=5x+5 | | -2(3x+4)-x+6=-5x-2(x+1)+5 | | 40+4x=8(1+x) | | -85.53+(-41.00)= | | 2(m+2)=64 |